Morphological response of native maize (Zea mays L.) seedlings to contrasting nitrogen environments - Reyes-Matamoros, Jenaro; Mora-Ramírez, Marco; Morales-Manzo, Ivan; Valderrama-Romero, Antonio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Nitrogen plays a vital role in plant metabolism, influencing growth and development, particularly in crops like maize (Zea mays L.). This study aimed to evaluate the morphological response of maize seedlings to different nitrogen levels. The design was a completely randomized factorial arrangement of 4 x 2, involving four maize cultivars and two nitrogen levels.The variety Sb 302 Berentsen and three native varieties originating from Tecamachalco, Puebla, Mexico were studied. For a period of 14, 21, 28 and 35 days, seedlings were grown in nutrient solution with 10 % and 100 % nitrogen levels under hydroponic conditions. The results revealed significant variability in seedling morphology, particularly in root architecture and dry weight, between the 10 % and 100 % nitrogen treatments. High coefficients of variation were observed in the lengths of crown and seminal roots, alongside significant correlations between root and seedling dry weights at both nitrogen levels. Additionally, a strong correlation was found between root length and number under the 10 % nitrogen treatment. The results highlight the critical role of nitrogen in maize seedling development and the interaction between nitrogen concentration and maize variety, particularly in primary root length. The study improves understanding of nitrogen’s role in optimizing maize growth and suggests strategies to enhance nitrogen use efficiency across different maize varieties.